Informational society : an economic theory of discovery, invention and innovation - Norman, Alfred Lorn; SpringerLink (online služba) (Boston, MA : Springer US, 1993)
Society continually promotes and adjusts to technological change. While mainstream economic thought assumes tastes and technology as given, it has had little to say about how society has promoted and adjusted to technological change. The book presents a utopian design for society in the 21st century whose purpose is to promote discovery, invention and innovation, which have become the principal aspects of national state competition.
Discovery, Invention and Innovation -- The Past -- Microbinics -- Forecast -- The Community -- The Economy -- Information Policy -- The Federal Government -- Governmental Decentralization -- The Individual.
Elektronická reprodukce.
Keywords: informační společnost; informační technologie -- ekonomické aspekty; informační technologie -- sociální aspekty; information society; information technology -- economic aspects; information technology -- socila aspects; monografie; elektronické knihy; e-knihy online; monographs; electronic books; e-books online